Neurological Manifestations in Falciparum Malaria: A Study in Tribal Community of Hill Tracts (Community Based Medical Journal, 2015)
Objectives  The aim of this study is to find out the prevalence and outcome of falciparum malaria with neurological manifestations.Materials and Methods  A prospective cross-sectional hospital-based study of 318 falciparum malaria patients using simple, direct, standardized questionnaire with history, lab investigations and neurological examination from January 2014 to December 2014.Results  July was the most vulnerable month for falciparum malaria causing the highest hospital admission (48.8%) and death (29.3%). The commonest age group affected was 15-30 years (49.2%). Prevalence of neurological manifestations was 41.2%. Altered sensorium (48.7%) was the most frequent neurological manifestation, followed by abnormal behavior (19.8%) and convulsions (15.5%). Case fatality rate was very high with neurological manifestations, highest with altered sensorium (31.3%). Perception of neurological manifestations among tribal was very poor. Primary health care providers also failed to diagnose most of the cases (69%) which presented with neurological features.Conclusion  Falciparum malaria with neurological involvement is associated with increased mortality. By documenting different neurological patterns of falciparum malaria and by trained health care personnel, mortality and morbidity rates can be reduced by early diagnosis and management.CBMJ 2015 January: Vol. 04 No. 01 P: 18-21